Have lifetime fertility intentions declined during the Great Recession? - Maria Rita Testa; Stuart Basten (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2012)
Using several rounds of the Eurobarometer [EB] survey, we examine the relationship between lifetime fertility intentions and the 'Great Recession' in Europe. We suppose that the increase in unemployment rates observed between 2006 and 2011, the years in which the two EB surveys were conducted, are key driving forces behind the decline of fertility intentions observed in some EU countries, like Greece, over the 5-year period. Our findings reveal that the increasing uncertainty attached to the reported fertility intentions substantially contributes to the declining pattern observed over the five years and that people who negatively assess the country economic situation are more likely to plan smaller family sizes than those who have a more optimistic view of the country past shortterm economic trend. Eventually, the aggregate negative changes occurred in fertility intentions between 2006 and 2011 are positively correlated with the increase of youth unemployment rates. We might expect a similar declining trend in lifetime fertility intentions also in other countries - such as Spain, Italy, Ireland and Portugal - in the years to come if the economic crisis starts to be perceived as heavily as in Greece in such countries.
Keywords: 300; Lifetime fertility intentions; Great Recession; multilevel analysis; Europe; unemployment rates; PIIGS; Fertilität; Familienplanung; Konjunktur; EU-Staaten